Governing the empire : provincial administration in the Almohad Caliphate (1224-1269) : critical edition, translation, and study of Manuscript 4752 of the Hasaniyya Library in Rabat containing 77 taqādīm ("appointments") - Buresi, Pascal. (Studies in the History and Society of the Maghrib, 2013)
In this book, Pascal Buresi and Hicham El Aallaoui edit, translate, and study an Arabic manuscript of the Royal Library of Rabat, containing 77 appointments of provincial officials. The Almohad Caliphs were the first Berbers to unite the whole Maghrib and the Iberian Peninsula under an imperial ideology elaborated at the end of the 12th C.E. by the most famous scholars, such as Averroes. This peripheral Islamic dynasty produced a pragmatic documentation that provides exceptional information about the administrative, political, ideological, and religious organisation of the largest medieval European-African Empire. Buresi and El Aallaoui convincingly stress the importance of the literature of the Chancellery in renewing the history of power and authority in medieval Islamic lands.